Sedentary Behavior and Arterial Stiffness in Adults with and without Metabolic Syndrome - Bohn, Lucimere; Ramoa, Ana; Silva, Gustavo; Silva, Nuno; Abreu, Sandra Marlene; Ribeiro, Fernando; Boutouyrie, Pierre; Laurent, Stéphane; Oliveira, José (International Journal of Sports Medicine, 2017)
This study aimed to investigate whether sedentary time (Sed) and physical activity (PA) are associated with arterial stiffness in individuals with and without metabolic syndrome (MetS). This cross-sectional study comprised 197 individuals (47±13 years; 58% female) from a primary health care centre. Arterial stiffness was assessed using carotid-femoral pulse wave velocity (cfPWV). Metabolic syndrome was determined as clustering of at least 3 out of 5 risk factors (central obesity, hypertension, impaired glucose, triglycerides and high-density lipoprotein cholesterol). Daily PA was objectively assessed and classified in Sed, light and moderate-to-vigorous PA. Physical activity was used as a continuous variable for multiple regression analysis. For mean comparisons of cfPWV between subjects with and without MetS, a binary split at the median of Sed and PA was used. Sedentary time was associated with cfPWV (β=0.11; p=0.01) explaining 1.3% of its variance; independently of age (β=0.49; p<0.001), systolic blood pressure (β=0.27; p<0.001) and fasting glucose (β=0.19; p<0.001). Participants with MetS and more Sed had higher cfPWV than those with MetS and less Sed (9.9±1.0 vs. 8.9±1.0 m/s; p<0.05). Sedentary time is associated with cfPWV independently of age and metabolic risk factors. A higher Sed in MetS individuals lead to a worse arterial stiffness profile.
Keywords: pulse wave velocity; physical activity; sedentary behaviour; metabolic syndrome